2019
DOI: 10.3390/su11205687
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Sport Involvement on Support for Mega Sport Events: Why Does It Matter

Abstract: For residents of a city that hosts a mega sport event, sport involvement can be associated with their perceptions of the impacts and quality of life (QoL) gained from that event. The attributes of mega sport events, with multiple sports in one competition, are linked with the level of residents’ sport involvement, specifically their interest in and identification with sports, which can foster more positive perceptions and enhance the anticipated QoL from the games. Despite the importance of sport involvement o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 65 publications
0
28
0
1
Order By: Relevance
“…Many contributions in this area have focused their interest on the impact of mega-sports events (Olympic Games and Football World Cups) (e.g., Chi, Ouyang and Xu, 2018;Kim and Kaplanidou, 2019;Koenigstorfer and Preuss, 2019). Nevertheless, the social impact of other major sporting events has also been analysed, such as the Tour de France (Balduck, Maes and Buelens, 2011), the FIBA World Cup Spain 2014 (González-García, Parra, Calabuig and Añó, 2016), the Perth America's Cup (Soutar and Mcleod, 1993) and Valencia's (Llopis and Gil, 2011;Parra, Añó, Calabuig and Ayora, 2016), America's Cup Soccer Chile 2015 (Parra, Alonso-Dos-Santos and Duclos, 2018a), the Barcelona World Race (Parra, Elasri, Triadó and Aparicio, 2016), the Australian Open tennis (Fredline, 2005), Kaohsiung World Games (Ma et al, 2013) and the Super Bowl (Kim and Walker, 2012;Lee and Krohn, 2013).…”
Section: Social Impact Of Motor Sport Eventsmentioning
confidence: 99%
“…Many contributions in this area have focused their interest on the impact of mega-sports events (Olympic Games and Football World Cups) (e.g., Chi, Ouyang and Xu, 2018;Kim and Kaplanidou, 2019;Koenigstorfer and Preuss, 2019). Nevertheless, the social impact of other major sporting events has also been analysed, such as the Tour de France (Balduck, Maes and Buelens, 2011), the FIBA World Cup Spain 2014 (González-García, Parra, Calabuig and Añó, 2016), the Perth America's Cup (Soutar and Mcleod, 1993) and Valencia's (Llopis and Gil, 2011;Parra, Añó, Calabuig and Ayora, 2016), America's Cup Soccer Chile 2015 (Parra, Alonso-Dos-Santos and Duclos, 2018a), the Barcelona World Race (Parra, Elasri, Triadó and Aparicio, 2016), the Australian Open tennis (Fredline, 2005), Kaohsiung World Games (Ma et al, 2013) and the Super Bowl (Kim and Walker, 2012;Lee and Krohn, 2013).…”
Section: Social Impact Of Motor Sport Eventsmentioning
confidence: 99%
“…It is, therefore, particularly important that organizations within the non-profit sport sector-such as federations-demonstrate sustainability, safety, and integrity [1]. Sponsors at every level want to be sure they are not aligning themselves with organizations that present a reputational risk, and federations as non-profit sporting organizations need financial support from public and private institutions to organize sporting activities [2,3]. Today, if federations want to receive that support their activity must be sustainable.…”
Section: Introductionmentioning
confidence: 99%
“…Reportedly, technical personnel rank second after service personnel, whereas Liu reported that management personnel ranked first through CGSS data, followed by secondary occupation personnel [13]. Of note, it is easy to see the effect of occupation on access to resources and that watching sports programs in action has almost no resource barriers [14].…”
Section: Introductionmentioning
confidence: 99%